PANGEAN SILAT EXISTENCE AS THE REALIZATION OF CULTURE IN THE VILLAGE SIMANDOLAK SUB BENAI KUANTAN SINGINGI - Hari Juliandro; Ahmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is motivated by the presence in the village of Silat Pangean Simandolak less preserved by the community. The problems that arise from this research is how the presence in the village of Silat Pangean Simandolak and how to describe the social practices of the theory of habitus, and the realm of capital based on the theory of Bourdieu. The purpose of this study was to determine the presence in the village of Silat Pangean Simandolak and to describe social practices silat Pangean views of the concept of habitus social practice, the realm and the capital. The location of this research was conducted at the sub-district Simandolak Benai Singingi Kuantan District. The method used in this study using a qualitative descriptive study. As informants as much as five (5) persons consisting of 2 (two) Pangean martial arts teacher, one village head and two students who study martial Pangean, while data collection technique using observation, interview by giving the question sheet and documentation. In analyzing the data from this study used a qualitative descriptive analysis method, while the validity of the data using triangulation techniques.The research found that the existence of martial Pangean still performed every 1 Shawwal according to the agreement for generations and become a tradition that must be preserved, this is done in the field of martial Pangean open and witnessed by the public, to show capital raised from the public and local government.Keywords: Silat Pangean, Local Culture, Tradition and Society